Morphophonemic Analysis of the Novel Ingkar by Boy Candra: Phoneme Changes, Phoneme Additions, and Phoneme Deletions - Duwi Andinis; Wahyu Widayati; Simanjuntak, Nensy Megawati (Journal of Language and Literature Studies, 2024)
Along with the times and advances in technology, language is also experiencing changes which result in the formation of new vocabulary and new variations of morphemes. To understand the process of change, researchers are encouraged to conduct research in the field of morphophonemics. This study examines the morphophonemic processes in Boy Candra's novel "Ingkar," focusing on phoneme changes, additions, and disappearances. This research focuses more on the morphophonemic processes in the prefixes meN- and peN. This study is done in qualitative ways because information is obtained by describing words or sentences that contain morphophonemic processes. The research instrument is the researcher himself with the help of an indicator table to make it easier for the researcher to process the data. The data collection technique is in the form of a listening technique, with basic tapping techniques and advanced techniques, namely proficient free-involved listening. The findings align with Ramlan's theoretical framework, which outlines specific phoneme transformations based on morpheme interactions. Key observations include the transformation of the phoneme /n/ to /m/ when meN- and peN- join words with certain prefixes, and the addition of phonemes in specific morphological environments. These patterns illustrate the dynamic interplay between morphology and phonology in Indonesian. The recommendations for further research suggest comparative analyses across different genres and dialects, as well as cognitive and psycholinguistic studies to deepen understanding of morphophonemic processing. This research contributes to a comprehensive understanding of morphophonemics in Indonesian, with implications for linguistic theory, language teaching, and computational applications.